Evaluation of lignan (-)-cubebin extracted from Piper cubeba on human colon adenocarcinoma cells (HT29) - Niwa, Andressa Megumi; Paula, Natalia Aparecida de; Vesenick, Diogo Campos; Sartori, Daniele; Maistro, Edson Luis [UNESP]; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mario Sergio (Taylor & Francis Inc, 2016)
The dibenzylbutyrolactone lignan (-)-cubebin, which is extracted from the seeds of the pepper Piper cubeba, has shown promise as an anti-inflammatory, analgesic, leishmanicidal, antiproliferative, and trypanocidal compound. Given the therapeutic potential of (-)-cubebin, this study aimed to investigate its safety profile by analyzing cytotoxicity, mutagenicity, cell proliferation kinetics, induction of apoptosis, and expression of pro-apoptotic genes in human colon adenocarcinoma cells (HT29) exposed to (-)-cubebin. MTT cytotoxicity assays demonstrated that (-)-cubebin was cytotoxic only at 280 mu M, whereas it was not cytotoxic at 2.8, 14, or 28 mu M. Data demonstrated that (-)-cubebin was not mutagenic as evidenced by a micronucleus (MN) assay, did not alter cell-growth kinetics over 4 d, and showed absence of induced apoptosis after 24 h. Further, CASP8 and CASP9 gene expression was not markedly changed in HT29 cells exposed to 28 mu M or 70 mu M (-)-cubebin for 12 h. Based on our observations, (-)-cubebin was cytotoxic at a concentration of 280 mu M, suggesting that the use of this concentration should be avoided. However, lower concentrations exerted no apparent damaging effects, indicating that this lignan is safe to use for pharmacological purposes at certain concentrations.